Things, Facts and Events - Faye, Jan,; Scheffler, Uwe,; Urchs, Max, (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
The volume deals with ontological and semantical issues concerning things, facts and events. Ontology tells us about what there is, whereas semantics provides answers to how we refer to what there is. Basic ontological categories are commonly accepted along with basic linguistic types, and linguistic types are accepted as basic if and because they refer to acknowledged ontological categories. In that sense, both disciplines are concerned with structure - the structure of the world and the structure of our language. An extended introduction overviews the topic as a whole, presenting in detail its history and the main contemporary approaches and discussions. More than 20 contributions by internationally acknowledged scholars make the volume a comprehensive study of some very fundamental philosophical entities.